Mutational analysis of the three cysteines and active-site aspartic acid 103 of ketosteroid isomerase from Pseudomonas putida biotype B. - Kim, S W (1997)
In order to clarify the roles of three cysteines in ketosteroid isomerase (KSI) from Pseudomonas putida biotype B, each of the cysteine residues has been changed to a serine residue (C69S, C81S, and C97S) by site-directed mutagenesis. All cysteine mutations caused only a slight decrease in the k(cat) value, with no significant change of Km for the substrate. Even modification of the sulfhydryl group with 5,5'-dithiobis(2-nitrobenzoic acid) has almost no effect on enzyme activity. These results demonstrate that none of the cysteines in the KSI from P. putida is critical for catalytic activity, contrary to the previous identification of a cysteine in an active-site-directed photoinactivation study of KSI. Based on the three-dimensional structures of KSIs with and without dienolate intermediate analog equilenin, as determined by X-ray crystallography at high resolution, Asp-103 was found to be located within the range of the hydrogen bond to the equilenin. To assess the role of Asp-103 in catalysis, Asp-103 has been replaced with either asparagine (D103N) or alanine (D103A) by site-directed mutagenesis. For D103A mutant KSI there was a significant decrease in the k(cat) value: the k(cat) of the mutant was 85-fold lower than that of the wild-type enzyme; however, for the D103N mutant, which retained some hydrogen bonding capability, there was a minor decrease in the k(cat) value. These findings support the idea that aspartic acid 103 in the active site is an essential catalytic residue involved in catalysis by hydrogen bonding to the dienolate intermediate.